Encouraging employees' voice behavior through Islamic work ethics: The role of team cohesion - Achmadi Achmadi; Swarmilah Hariani; Isah Shehu Mohammed (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2023)
The current study aims to open new insights into employee voice through religiosity and team cohesion approaches. Specifically, this study examines the effect of Islamic work ethics (IWE) as an antecedent of team cohesion and employee voice. The research model includes the intermediate and moderator roles of team cohesion to provide a more comprehensive insight into explaining the voice of employees through IWE. The data were collected from 227 university lecturers using a time-lagged approach; the model was analyzed with PLS-SEM. The analysis results confirmed all hypotheses where IWE is positively related to team cohesion and employee voice. Additionally, it has been demonstrated that team cohesion determines employee voice, mediation, and moderation in the relationship between IWE and employee voice. Public interest statement Employees can provide helpful information regarding work procedures, difficulties encountered, and areas for development. Companies may utilize their insights to identify current issues, examine their origins, and develop more efficient solutions by incorporating people in problem-solving and decision-making. This study offers new insights into studying employee voice through a religious approach (IWE) and team cohesion. Article historyReceived: 5/3/2023 | Revised: 5/28/2023 | Accepted: 5/28/2023 | Online First: 5/29/2023